1998
DOI: 10.1128/aac.42.12.3245
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Resistance to Azole Drugs in Trypanosoma cruzi

Abstract: Trypanosoma cruzi is the protozoan parasite that causes Chagas’ disease, a frequently fatal illness affecting the heart and gastrointestinal systems. An estimated 16 million to 18 million people in Latin America and 50,000 to 100,000 people in the United States are infected with this pathogen. Treatment options for T. cruziinfections are suboptimal due to the toxicities and limited effectiveness of the available drugs. Azole antimicrobial agents have been discovered to have antitrypanosomal activity by inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…On the other hand, we found that BZ-resistance parasites presented cross-resistance to NFX (Figure 1B), based upon previous experimental evidence where it was confirmed that resistance could be shared among similar nitroheterocyclic compounds of induced and natural resistance parasites [15,54-56]. However, G418 susceptibility did not show differences within all the phenotypes (Figure 1C).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, we found that BZ-resistance parasites presented cross-resistance to NFX (Figure 1B), based upon previous experimental evidence where it was confirmed that resistance could be shared among similar nitroheterocyclic compounds of induced and natural resistance parasites [15,54-56]. However, G418 susceptibility did not show differences within all the phenotypes (Figure 1C).…”
Section: Discussionsupporting
confidence: 79%
“…The stability of the resistant phenotype has been confirmed in many in vitro and in vivo models through different parasite species [19,54]. This condition is the result of many cases of stable genetic alterations such as mutations, amplifications and deletions [16,18,58].…”
Section: Discussionmentioning
confidence: 99%
“…Variation in susceptibility to nitroheterocyclics can also be due to emergence of resistance within a population; indeed, it is well known that drug-resistant T. cruzi can be easily generated in the laboratory405455, and a recent study proposed that T. cruzi genome plasticity underlies quick selection of phenotypes resistant to benznidazole56. However, the most important point may be the way resistance is defined: if one considers EC 50s – defined as the compound concentration that reduces infection by 50% – as a parameter to measure resistance, our study confirms findings that there are differences in susceptibility to benznidazole, nifurtimox, and fexinidazole sulfone (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1011 However, all of these lead compounds are azoles, and there is an emerging issue of the rapid appearance of laboratory-induced resistance to azoles in T. cruzi cell culture. 12 Thus, the development of therapeutics with different scaffolds targeting Tc CYP51 is an important undertaking.…”
Section: Introductionmentioning
confidence: 99%